Clinical features and outcomes of asymptomatic pulmonary sarcoidosis. A comparative cohort study. (August 2020) - Iriarte, Adriana; Rubio-Rivas, Manuel; Villalba, Nadia; Corbella, Xavier; Mañá, Juan
Abstract: Objective: To evaluate the clinical characteristics and outcomes of patients with asymptomatic pulmonary sarcoidosis (APS) detected incidentally and compare them with symptomatic non-Löfgren sarcoidosis (SnLS) patients. Methods: Patients diagnosed as having APS at a University hospital in Barcelona, Spain, followed prospectively from 1976 to 2018. APS was defined as the presence of bilateral hilar lymphadenopathy (BHL) with or without lung parenchymal involvement discovered incidentally on chest radiograph or CT scan. APS was compared with SnLS. Results: APS was diagnosed in 50 (13.6%) and SnLS in 317 (86.4%) patients. At diagnosis, stage I chest radiograph was significantly more frequent in APS than in SnLS (p < 0.001) and there were no asymptomatic patients with stages III and IV. SnLS showed more severe impairment in FVC (p = 0.009) and forced expiratory volume in 1st second (FEV1) (p = 0.003) than APS, while DLco was similar in both groups. Extrathoracic involvement at diagnosis and during the follow up was less frequent in APS than in SnLS patients (p < 0.005). Endobronchial ultrasonography-guided transbronchial needle aspiration (EBUS) was the most used diagnostic tool. Treatment was more frequently required in the SnLS than in APS (p < 0.001). At five years, APS patients showed less presence of active disease than SnLS (p = 0.054). Conclusions: APS showed earlier radiological stages, lesser impairment in lung function, extrapulmonary organ involvement and need for treatment than SnLS. EBUS was the most useful diagnostic tool. In spite of its benign presentation, around one third of patients evolved to persistent disease but usually with mild clinical and functional impairment. Highlights: Asymptomatic pulmonary sarcoidosis detected incidentally is not infrequent. Stage I chest radiograph is the most common presentation. Lung functional impairment was less frequent than in symptomatic patients. Extrapulmonary involvement was less frequent than in symptomatic patients. Persistent disease was less frequent than in symptomatic patients.